Fraud Triangle, Integritas, dan Penggunaan Teknologi Informasi terhadap Kecurangan Akademik Masa Pandemi Covid-19 - Kusumayanti, Ni Putu Diah; Utama, I Made Karya (Fakultas Ekonomi Universitas Samudra, 2024)
The aim of this research is to analyze how the fraud triangle, student integrity, and the use of information technology influence academic cheating behavior among students during the Covid-19 pandemic. This research was conducted at the Faculty of Economics and Business, Udayana University, with a total sample of 280 active accounting students selected using a purposive sampling approach and analyzed using multiple linear regression analysis. Empirical results found that the fraud triangle and the use of information technology have a positive influence on academic cheating behavior, which means that when pressure, opportunity, rationalization, and use of information technology increase, cheating activities will also increase. Student integrity, on the other hand, has a negative influence on academic cheating behavior.